2011
DOI: 10.1002/lt.22227
|View full text |Cite
|
Sign up to set email alerts
|

Release of cytokines and hemodynamic instability during the reperfusion of a liver graft

Abstract: The objectives of this prospective, observational study were (1) to determine whether a transplanted liver graft releases proinflammatory cytokines into the systemic circulation upon reperfusion and (2) to determine whether they contribute to any subsequent hemodynamic instability observed after graft reperfusion (if this release occurs). Blood samples from 17 consecutive patients undergoing liver transplantation were analyzed for cytokines, including tumor necrosis factor a (TNFa), interleukin-1b (IL-1b), IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 22 publications
2
43
1
1
Order By: Relevance
“…Activated neutrophils release enzymes and cytokines into the subendothelial space, directly causing kidney injury and the recruitment of monocytes and macrophages . Cytokine release from the liver after cold storage has been shown by Bezinover et al, and additional analysis revealed that the levels of cytokines were higher in grafts from higher‐risk donors . In a pig model, we showed that cytokine release and Kupffer cell activation was also higher in DCD livers exposed to increased warm ischemia times, resulting in increased HIRI and PNF .…”
Section: Discussionsupporting
confidence: 63%
“…Activated neutrophils release enzymes and cytokines into the subendothelial space, directly causing kidney injury and the recruitment of monocytes and macrophages . Cytokine release from the liver after cold storage has been shown by Bezinover et al, and additional analysis revealed that the levels of cytokines were higher in grafts from higher‐risk donors . In a pig model, we showed that cytokine release and Kupffer cell activation was also higher in DCD livers exposed to increased warm ischemia times, resulting in increased HIRI and PNF .…”
Section: Discussionsupporting
confidence: 63%
“…During LT, on the reperfusion of the implanted liver, the graft itself can release substances such as proinflammatory cytokines [3,30,31] and nitric oxide [32], which can lead to the imbalance between vasoconstrictive and vasodilative factors and subsequently disturbance the adapt capacity of vascular resistance and renal vascular dilates [31,33]. Furthermore, this reduction of tone within renal might overwhelm the elevated renal RI values related to leukocyte activation and infiltration, renal tubular injury and renal edema.…”
Section: Discussionmentioning
confidence: 99%
“…In transplant, a unique situation occurs in which the cytokine profile of the donor allograft combines with that of the recipient, as cytokines produced in the donor allograft are likely to be flushed into the patient's circulating blood during reperfusion. It has been shown that donor-derived cytokines contribute to hemodynamic instability during reperfusion (29), which could affect IRI severity. To determine the contribution of the donor organ to cytokine release and patient IRI status, we directly compared blood samples obtained from the recipient's portal blood before or after reperfusing the donor organ as well as characterizing cytokine profiles of systemic blood samples obtained from recipients after transplant.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%